1994
DOI: 10.1038/npp.1994.1
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Clozapine on Plasma Norepinephrine: Relationship to Clinical Efficacy

Abstract: Clozapine is an atypical neuroleptic medication with superior efficacy to conventional antipsychotic agents for patients with chronic, symptomatic schizophrenia. Neurochemical characteristics that distinguish clozapine from other neuroleptics and contribute to its differential efficacy are not known. We assessed the effects of clozapine on plasma levels of norepinephrine (NE) in a double-blind, parallel groups comparison of clozapine (n = 11) and haloperidol (n = 15) in chronic schizophrenic outpatients who ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
71
0
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 109 publications
(78 citation statements)
references
References 12 publications
6
71
0
1
Order By: Relevance
“…On the other hand, as with clozapine, risperidone did not alter DOPA and DOPAC levels, or the time-related changes in the 3 H-DHPG/ 3 H-NE ratio following 3 H-NE infusion. Although some prior clinical studies support the noradrenergic system's involvement in the treatment response to clozapine (Breier et al 1994b;Schulz et al 1997;Fleischhaker et al 1998), no such data are available for risperidone (See et al 1999), and no inferences can be made about risperidone's therapeutic mechanisms of action from this investigation that was primarily focused on its pharmacokinetic effects. Nonetheless, peripheral NE measures are important because a considerable amount of animal data, where peripheral and central measures were collected simultaneously in the presence of an effective blood-brain barrier, suggest that plasma measures may reflect directionally similar changes in the brain (Ziegler et al 1977; Jimerson et al Figure 1.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…On the other hand, as with clozapine, risperidone did not alter DOPA and DOPAC levels, or the time-related changes in the 3 H-DHPG/ 3 H-NE ratio following 3 H-NE infusion. Although some prior clinical studies support the noradrenergic system's involvement in the treatment response to clozapine (Breier et al 1994b;Schulz et al 1997;Fleischhaker et al 1998), no such data are available for risperidone (See et al 1999), and no inferences can be made about risperidone's therapeutic mechanisms of action from this investigation that was primarily focused on its pharmacokinetic effects. Nonetheless, peripheral NE measures are important because a considerable amount of animal data, where peripheral and central measures were collected simultaneously in the presence of an effective blood-brain barrier, suggest that plasma measures may reflect directionally similar changes in the brain (Ziegler et al 1977; Jimerson et al Figure 1.…”
Section: Discussionmentioning
confidence: 95%
“…Our previous work suggested that clozapine has complex effects on the noradrenergic system, producing a robust increase in NE, but without an expected proportional increase in DHPG (Breier et al 1994b;Elman et al 1999). We hypothesized, based on the receptor binding profile of risperidone, that patients treated with the drug would display different characteristics of the noradrenergic response than their clozapine-treated counterparts.…”
mentioning
confidence: 96%
See 3 more Smart Citations